Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.soard.2021.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of bariatric surgery in a COVID-19 era: a review of economic costs

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…The planning of adequate pathways allows on the one hand to reduce the rate of infections and on the other guarantees the use of health resources for the restoration of elective surgical activity. The reduction of surgical activities could represent a significant pitfall for public health expenditure, entailing a potentially greater cost than managing the patient with SARS-CoV-2 [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The planning of adequate pathways allows on the one hand to reduce the rate of infections and on the other guarantees the use of health resources for the restoration of elective surgical activity. The reduction of surgical activities could represent a significant pitfall for public health expenditure, entailing a potentially greater cost than managing the patient with SARS-CoV-2 [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this context, bariatric surgery is essential in reducing obesity-related complications of SARS-CoV-2 infection. Specifically, a multicenter study showed that patients who had undergone bariatric surgery at least 12 months earlier developed COVID-19 in less severe forms than obese patients not treated with bariatric surgery [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, a report by the McKinsey Global Institute estimated that the economic impact on the world economy due to obesity amounts to US$2 trillion, equivalent to 2.8% of global gross domestic product (GDP) [ 16 ]. In this era, when it is becoming increasingly important to pay attention to the distribution of health care investments and beyond, it seems clear that proper care of patients with obesity is necessary to derive an economic benefit as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis by Liu et al [ 2 ] revealed that postponement of in-person clinical care affected the management of patients with chronic diseases, such as the postponement of bariatric surgeries for chronic obesity [ 3 ]. A worldwide survey of bariatric surgeons revealed that 84.6% had postponed primary or redo bariatric procedures under COVID-19 restrictions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%